Inhibition of IkappaB kinase alpha (IKKα) or IKKbeta (IKKβ) plus forkhead box O (Foxo) abolishes skeletal muscle atrophy - Reed, S.A. (2011)
Two transcription factor families that are activated during multiple conditions of skeletal muscle wasting are nuclear factor κB (NF-κB) and forkhead box O (Foxo). There is clear evidence that both NF-κB and Foxo activation are sufficient to cause muscle fiber atrophy and they are individually required for at least half of the fiber atrophy during muscle disuse, but there is no work determining the combined effect of inhibiting these factors during a physiological condition of muscle atrophy. Here, we determined whether inhibition of Foxo activation plus inhibition of NF-κB activation, the latter by blocking the upstream inhibitor of kappaB kinases (IKKα and IKKβ), would prevent muscle atrophy induced by 7 days of cast immobilization. Results were based on measurements of mean fiber cross-sectional area (CSA) from 72 muscles transfected with 5 different mutant expression plasmids or plasmid combinations. Immobilization caused a 47% decrease in fiber CSA in muscles injected with control plasmids. Fibers from immobilized muscles transfected with dominant negative (d.n.) IKKα-EGFP, d.n. IKKβ-EGFP or d.n. Foxo-DsRed showed a 22%, 57%, and 76% inhibition of atrophy, respectively. Co-expression of d.n. IKKα-EGFP and d.n. Foxo-DsRed significantly inhibited 89% of the immobilization-induced fiber atrophy. Similarly, co-expression of d.n. IKKβ-EGFP and d.n. Foxo-DsRed inhibited the immobilization-induced fiber atrophy by 95%. These findings demonstrate that the combined effects of inhibiting immobilization-induced NF-κB and Foxo transcriptional activity has an additive effect on preventing immobilization-induced atrophy, indicating that NF-κB and Foxo have a cumulative effect on atrophy signaling and/or atrophy gene expression.